Towards enhanced varistor property and lower dielectric loss of CaCu3Ti4O12 based ceramics. (15th February 2016) - Li, Jianying; Wu, Kangning; Jia, Ran; Hou, Linlin; Gao, Lu; Li, Shengtao
Abstract: A novel (1 −  x )CaCu3 Ti4 O12  −  x Y2/3 Cu3 Ti4 O12 composite ceramic was developed. Two perovskite-like grains, i.e. CaCu3 Ti4 O12 grains of 1–2 μm and Y2/3 Cu3 Ti4 O12 grains of 4–6 μm, can be both detected in the samples. High Schottcky barrier height and grain boundary resistance were formed via combining these two perovskite-like phases, which plays the critical role on the varistor and dielectric performance. Greatly enhanced nonlinear coefficient of 9.88 and very low dielectric loss of 0.02 can be achieved in the composite ceramics accompanied with the permittivity of ~ 2000, compared with reported results of 2–6 and 0.05–0.8 for general CaCu3 Ti4 O12 ceramics. This varistor–capacitor multifunctional characteristic makes it a promising material in the field of over voltage protections of electronic devices. Graphical abstract: Highlights: Nonlinear coefficient of CaCu3 Ti4 O12 ceramics was greatly increased to 9.88 with low loss of 0.02. Enhanced barrier height and resistance were formed via combining composite grains. A promising candidate for over voltage protection of electronic system.